Types of fairy tales and their importance in child development. "Fairytales - leads to goodness" (Folk word) (Eurasian Scientific Herald, 2023)
This article provides information about the types of fairy tales, their importance in the development of the child's psyche and speech. This article can be used by parents, educators, students and independent researchers.